Performance improvements in polymer nanofiber/fullerene solar cells with external electric field treatment - Solanki, Ankur (2015)
Organic solar cell (OSC) devices based on predominantly poly(3-hexylthiophene-2,5-diyl) (P3HT) nanofibers (NFs) exhibit inferior device performance compared to that of their conventional nanodomain P3HT:PCBM systems, which is credited to the low interfibrillar mobility between the NFs [Kurniawan, M.; et al. J. Phys. Chem. C2012, 116, 18015]. To improve the charge transport of these devices, external electric field (E-field) treatment of the active layer is performed in a bid to align the random polymer chains between the NFs perpendicular to the electrode. Extensive device testing revealed a 22.7% improvement in power conversion efficiency and higher mobilities (37.5% improvement) for the E-field-treated devices compared to those for the control. Transient absorption spectroscopy shows an improved initial generation of carriers and formation of polarons in the E-field-treated samples over those in the control samples in the femtosecond–nanosecond time scale. However, in the absence of any sweep-out voltage in the E-field-treated films, a higher recombination rate in the nanosecond–microsecond time scale is observed. Concomitant with the improved device efficiencies and higher mobilities measured in the E-field-treated devices and the higher recombination rate over the nanosecond–microsecond time scale in the E-field-treated films, we assert that the E-field treatment improved charge mobility and transport of P3HT-NF:PCBM through improved orientation of the polymer chains in the amorphous P3HT phase coexisting with the NFs.